Use of Ceftriaxone as a Predictor of Good Outcome in Stroke Patients: A Retrospective Chart Review. Issue 2 (April 2022) - Dev, Priya; Singh, Varun Kumar; Kumar, Anand; Chaurasia, Rameshwar Nath; Singh, Neelima Alka; Gautam, Priyanka; Dhimani, Neetu Rani; Mishra, Vijaya Nath; Joshi, Deepika; Pathak, Abhishek
Background: Whether ceftriaxone (CEFT) has any added advantage other than its antibiotics effect in stroke as a neuroprotective agent is not known, and this forms the base of this study. Purpose: We tried to assess the predictive role of the use of CEFT with respect to outcome in stroke patients. Methods: A retrospective chart review was conducted from a stroke registry over consecutive stroke patients admitted at a tertiary teaching institute from January 2017 to December 2018. Patients were categorized into three groups on the basis of antibiotics they received; patients without antibiotic treatment (NAB), piperacillin plus tazobactam treatment, and the CEFT treatment group. The outcome was assessed by the modified Rankin Scale at three months in good (0–3) and poor outcomes (4–6). Results: A total of 390 stroke patients were analyzed with ages ranging between 20 and 95 years and 151 of them were females. It was found that the severity at three months was significantly lower in those patients who were given CEFT antibiotic ( P = 0.04; OR = 0.626; 95% CI [0.396, 0.990]). Conclusion: Stroke patients in CEFT-treated group have a better outcome compared to piperacillin–tazobactam therapy or without antibiotics use at three months. This study indicates the possibility of an additional neuroprotective effect of CEFT apart from its antibacterial property.